Ka-band time-domain multiplexing front-end with minimum switch area utilization on 22 nm fully depleted silicon-on-insulator CMOS technology. Issue 7 (31st March 2021) - Hietanen, Mikko; Rusanen, Jere; Aikio, Janne P.; Tervo, Nuutti; Rahkonen, Timo; Pärssinen, Aarno
Abstract: A time-domain duplexing radio frequency (RF) front-end with integrated antenna switch, power amplifier (PA), and low noise amplifier (LNA) was developed aiming for fifth-generation communication (5G) applications covering 24–28 GHz frequency range. Antenna switch utilizes pre-existing LNA input matching network together embedded with grounded shunt transistor switch to provide sufficient isolation of receive side from PA. Respectively, high impedance of off-state PA is assumed to achieve acceptable receive performance. Resulting output power is 13.6 dBm with 15 dB of peak small-signal gain at 28 GHz. Maximum average channel power was 4.8 dBm with 100 MHz 64-QAM OFDM signal within 5G adjacent channel power ratio and error vector magnitude specifications. Receive (RX) front-end achieves 5 dB noise figure at 24 GHz and 7 dB of peak gain. Performances of amplifiers degraded only by 2 dB from switch integration. The front-end dissipates 183 and 4.6 mW of power in transmit and receive mode, respectively. The simplistic design method minimizes cost both in circuit area (only 0.19 mm 2 ) and design time making this front-end an attractive alternative in massive phased array applications using 22 nm complementary metal oxide semiconductor (CMOS) fully depleted silicon on insulator process.